Skillnader i dibeteende mellan raserna Svensk och Holländsk Yorkshire - i digivningsboxar där smågrisarna har tillgång till suggan och smågrisarna i grannboxen - Lundahl, Isabel (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
In Sweden we produced 2,6 million slaughter pigs last year (2018). In 2012, the Swedish Yorkshire was exchanged with Dutch Yorkshire in Sweden because of economic reasons and the effective breeding development within the Dutch breed. However, Dutch Yorkshire has through breeding been adapted to be kept “fixed” through farrowing and lactation. In contrast, the Swedish Yorkshire has through breeding been adapted to be held loose housed during farrowing and lactation.